KONSEP MODERASI BERAGAMA PADA ANAK USIA DINI - Wahab, Gusnarib; Kahar, M. Iksan (Musawa: Journal for Gender Studies, 2023)
Early Childhood Education as the main basis of education for an individual should be able to build and integrate a tolerant attitude towards plural social life contained in the Islamic values of moderation, where these values must be applied and become a habit for a child who will grow into a person who has a tolerant attitude towards differences. If young children are not introduced to the values of moderation, then when growing up they will be easily influenced and even influence liberal and extreme ideas which can later threaten disintegration in public life. Seeing the dangers of disintegration that continue to threaten today and the importance of implementing Islamic moderation values in early childhood.